KEDUDUKAN HUKUM PEMEGANG SAHAM YANG TIDAK MELAKUKAN PENYETORAN MODAL SECARA PENUH ATAS PEMBAGIAN DIVIDEN DALAM PERSEROAN TERBATAS - Indra Jaya Nata (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to find out about the legal standing of shareholders who do not make a full capital deposit on dividend distribution in a limited liability company. This legal research is a normative legal research and the legal source used consists of primary legal material and secondary legal material, then analyzed by deductive method of silogism based on the mindset of the general to specific things, by connecting between the major premise and the minor premise is further drawn conclusively. The results of this legal research show that the legal standing of shareholders who do not make a full capital deposit causes the loss of shareholders' rights in accordance with Article 52 paragraph (1) of the UUPT including the right to obtain dividend distribution. Such rights will be obtained by shareholders after carrying out their obligations to deposit capital in full.